2014
DOI: 10.1016/j.snb.2013.12.072
|View full text |Cite
|
Sign up to set email alerts
|

Swelling and shrinking behaviour of photoresponsive phosphonium-based ionogel microstructures

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. KeywordsStimuli responsive, photo-responsive, mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…In these systems a much smaller gel feature size is typically used, which means the effect will be faster than presented in this paper, making the structures overall more practical to use in a reversible manner, and rendering them more attractive for use as actuators/valves in microfluidic systems. [40] …”
Section: Light Induced Shrinking and Reswelling Of The Gelsmentioning
confidence: 99%
“…In these systems a much smaller gel feature size is typically used, which means the effect will be faster than presented in this paper, making the structures overall more practical to use in a reversible manner, and rendering them more attractive for use as actuators/valves in microfluidic systems. [40] …”
Section: Light Induced Shrinking and Reswelling Of The Gelsmentioning
confidence: 99%
“…It was found that the ionogel typically contracts by 40 ± 1 % (n = 3) of its initial swollen state after white light irradiation for about 5 min ( Figure 3B). A stronger white light is required for shrinking of the ionogel-based actuator compared to that reported by Czugala et al 22 (Aigo Digital Microscope GE-5) and…”
Section: Characterisation Of Photo-switchable Actuators Swelling and mentioning
confidence: 78%
“…The rate constants of the shrinking process ksh (black line) were estimated using Eqn.3 and a value of 3.5 ± 0.6 10 -3 s -1 (n = 3). Czugala et al 22 reported the swelling and shrinking kinetics of 400 µm discs made of the same p(SPNIPAAm) ionogel. Faster swelling and shrinking constants, ksw of 4.5 ± 0.3 10 -2 s -1 and ksh 8.3 ± 0.9 10 -2 s -1 , respectively, were reported.…”
Section: Characterisation Of Photo-switchable Actuators Swelling and mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the [P 66614 ][NTf 2 ] ionogel allowed the highest degree of swelling. 254,255 Deguchi, Kohno and Ohno designed polyelectrolytes derived from tributyl-n-alkylphosphonium 3-sulfopropylmethacrylate-type IL monomers. Based on these compounds, chemically cross-linked polyelectrolyte gels were prepared, showing LCST-type phase changes.…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%